2022
DOI: 10.3390/ijerph191610401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute High-Intensity Interval Exercise and High-Intensity Continuous Exercise on Inhibitory Function of Overweight and Obese Children

Abstract: This study aimed to examine whether a single bout each of high-intensity interval exercise (HIIE) and high-intensity continuous exercise (HICE) could improve inhibitory functions of overweight and obese children, and which mode of exercise was more beneficial. Seventy-two overweight and obese children, with (26.02 ± 1.05 kg/m2), aged 10–14 years (11.56 ± 1.03 years), were randomly assigned to three groups. The HIIE group completed a 30-min treadmill exercise session (5-min warm up, 20-min HIIE, and 5-min cool-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Previous research from our lab also demonstrated faster response times in congruent and incongruent conditions of a Flanker task following acute HIIE when compared with task performance following a sedentary control session among 16 obese young adult men ( Xie et al., 2020 ). We found similar improvement in a Stroop task following HIIE ( Zhang et al., 2022 ), suggesting that a single bout of HIIE may facilitate cognitive function, and specifically inhibitory control among individuals with overweight and obesity.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Previous research from our lab also demonstrated faster response times in congruent and incongruent conditions of a Flanker task following acute HIIE when compared with task performance following a sedentary control session among 16 obese young adult men ( Xie et al., 2020 ). We found similar improvement in a Stroop task following HIIE ( Zhang et al., 2022 ), suggesting that a single bout of HIIE may facilitate cognitive function, and specifically inhibitory control among individuals with overweight and obesity.…”
Section: Introductionmentioning
confidence: 55%
“…Upon arrival, participants provided written informed consent and completed a demographic questionnaire. Intelligence (Digit Span test) ( Wechsler, 1997 ) as well as the eating styles (Dutch Eating Behavior Questionnaire (DEBQ) ( Van Strien et al., 1986 ) were then measured to characterize the study participants ( Chi et al., 2021 ; Khandekar et al., 2023 ; Song et al., 2022 ; Zhang et al., 2022 ). Subsequently, height and weight were assessed for the determination of BMI (weight (kg)/height (m) 2 ) and cardiorespiratory fitness (VO 2peak ) was assessed using the YMCA submaximal ergometer exercise test ( Golding et al., 1989 ; Xie et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…This meta-analysis synthesizes ndings from 20 studies published between 2010 and 2023, encompassing a total of 1161 overweight or obese participants (Table 1). Based on the exercise interventions employed across all studies, interventions were categorized into seven types: (1)Control training(CT): involving no exercise intervention, serving as a blank control group; (2) AE: comprising sustained aerobic activities such as running and cycling; 17,[31][32][33][34][35][36][37] (3)RT: involving resistance exercises using body weight or external equipment; 26,38 (3) CPA : incorporating multi-body part movements and/or interaction with objects, requiring precise timing and spatial estimation for goal-directed behavior, with included studies focusing mainly on rope skipping among children and adolescents; 25,39,40 (4) Prolonged time of exercise(PTE) : aimed at increasing participants' physical activity levels without specifying the type of exercise; 17,24,30,41 (5) High-intensity interval training(HIIT): involving repeated bouts of high-intensity training interspersed with active or passive recovery; 17,32,35 (6)AE combines RT (mix mode, MIX). 10,16,42 Most interventions lasted for at least 4 weeks, although three studies implemented a single session of exercise intervention.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…10,16,42 Most interventions lasted for at least 4 weeks, although three studies implemented a single session of exercise intervention. 25,30,32 Regarding the study population, approximately 522 (45%) were male participants, with one study exclusively including male subjects and three studies exclusively including female subjects, while the remaining 16 studies included both male and female participants. Among the included studies, 10 focused on children and adolescents aged 18 and under, 8 studies targeted adult populations aged 18 to 59, and 2 studies were conducted on individuals aged 60 and above.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nine studies were included in this study [15][22][23] [24][25][28] [29][45][58] (see Table 1), ve from China [23][24] [25][28] [45] and four from the United States [15][22][29][58] ; sixwere published to enter ve years [22][23] [24][25][28] [45] ; eight were randomized controlled trials [15][22][23] [24][25][28] [45][58] and one was non-randomized controlled [29] ; the sample size included in each study ranged from 35 to 206, for a total sample size of 764; subjects were between 8 and 16 years of age, with a BMI between 13 and 40.38, or a BMI ≧ 85%; all 9 papers reported the intervention modality, involving exercise modalities including: jump rope, basketball, soccer, running, dance, classroom-based academic physical education program (combiningexercise with math curriculum), and games; training intensity was moderate in 6 papers [15][24] [25][28] [29][58] , moderate to high intensity in 2 papers [22] [45] , and high intensity in 1 paper [23] ; duration ranged from 10 to 75 min, with 40 min beingthe majority; exercise duration, 5 articles for long-term intervention [15][22] [24][25] [45] and 4 articles for acute intervention [23][28] [29][58] ;the test tasks included: Flanker task, stroop task, more-odd shifting task, 2-Back task and Switch task, and the test indexes were all expressed in response time performance. Nine of the included publications were at moderate risk of bias.…”
Section: Basic Characteristics Of the Included Literaturementioning
confidence: 99%